An investigation of the information content of foreign sensitive payment disclosures - Smith, David B.; Stettler, Howard; Beedles, William (Journal of Accounting and Economics, 1984)
The study investigates the information content of the foreign sensitive payment disclosures made during the Securities and Exchange Commission's ‘voluntary’ disclosure program. The results of the information content tests and the tests of the relationship between payment size and abnormal security returns imply that investors may have been reacting to the expectation of the loss of future business or to the possibility of future government sanctions.